Short Communications : Efficiency and utility of pollination without emasculation (PWE) method in intra- and inter-specific hybridization in soybean - Shivakumar, M.; Gireesh, C.; Talukdar, Akshay (The Indian Journal of Genetics and Plant Breeding, 2016)
Efficiency and applicability of a new method of hybridization called ‘pollination without emasculation’ was evaluated in a set of crosses involving Glycine max and Glycine soja genotypes. The genotypes were crossed in various combinations to develop MAGIC (multiparent advanced generation intercross) and NAM (nested association mapping) population as well as to widen the genetic base of soybean through wide hybridization. Success of hybridization ranged from 33 % to 77% during kharif season. Number of false crossed seeds as measured through hybridity testing was negligible (0-15%). Rate of crossing success was more during kharif than rabi (17.33%) season. The PWE appeared to be highly efficient and applicable equally to intra-specific and inter-specific crosses in soybean.